2013
DOI: 10.1590/s1679-78252013000300010
|View full text |Cite
|
Sign up to set email alerts
|

A numerical simulation of metallic cylindrical sandwich shells subjected to air blast loading

Abstract: A numerical simulation of metallic cylindrical sandwich shells subjected to air blast loading INTRODUCTIONCellular metals including foams and honeycombs, as a new class of ultra-light multi-functional materials, are widely used as advanced structural components in many engineering applications due to their excellent physical, thermal and mechanical properties [1][2][3]. Extensive applications of cellular metals include light weight cores for sandwich structures to increase the shock resistance, and improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…In another study, Jing et al investigated cylindrical sandwich structures air blast response numerically. In the finite element model, finite shock conditions and nonlinear air compressibility are adopted according to Kambouchev-Noels-Radovitzky (KNR) theory, and weight optimization was conducted to redefine the face-sheet thickness, core thickness and core relative density [143]. A similar conclusion was stated by Li et al where they numerically investigated the blast performance of spherical sandwich panels and revealed that spherical sandwich panels showed better blast performance than cylindrical-shape panels [144].…”
Section: The Effect Of Radius Of Curvature Of Sandwich Panelmentioning
confidence: 70%
“…In another study, Jing et al investigated cylindrical sandwich structures air blast response numerically. In the finite element model, finite shock conditions and nonlinear air compressibility are adopted according to Kambouchev-Noels-Radovitzky (KNR) theory, and weight optimization was conducted to redefine the face-sheet thickness, core thickness and core relative density [143]. A similar conclusion was stated by Li et al where they numerically investigated the blast performance of spherical sandwich panels and revealed that spherical sandwich panels showed better blast performance than cylindrical-shape panels [144].…”
Section: The Effect Of Radius Of Curvature Of Sandwich Panelmentioning
confidence: 70%
“…Liu et al [16] used the numerical simulation to prove that a hollow cylindrical shells sandwich structure with a gradient metal foam core has a better blast resistance than hollow cylindrical shells without a gradient foam core. Through experiments and numerical simulations, Jing et al [17][18][19][20] studied the effect of geometric structure (i.e., panel thickness, the relative density of core layer, and sample curvature) on the energy absorption and destruction of cylindrical metal shells under dynamic loads. Pan et al [21] conducted a finite element analysis on the mechanical properties of the doublelayer aluminum foam sandwich curved panels.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the past research work has been carried out on the sandwich foam panels with different varieties of core ranging from fiber reinforced polymer (FRP), natural material (air, sand/soils), polymeric foams, honeycombs and commercially available metal foams (Hanssen et al, 2002aand 2002b, Qiu et al, 2003, Xue and Hutchinson, 2003, Radford et al, 2006, Sriram et al, 2006, NematNasser et al, 2007, Bahei-El-Din and Dvorak, 2008, Tekalur et al, 2008, Karagiozova et al, 2009, Zhu et al, 2009, Langdon et al, 2010, Jing et al, 2013, Chang et al, 2013, and Liu et al, 2013. No studies, however, have been reported on the stiffened sandwich foam panels and their blast response, except author's recent work on the response of stiffened polymer foam sandwich structures under impulsive loading (Goel et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%